Fundamental Values of Organizational Culture in Higher Education - Borozan, Maia; SADOVEI, Larisa; Turcan, Lilia; Mihai, Cristina (Didactica Danubiensis, 2025)
The research objectives refer to the analysis of the fundamental values that define organizational culture, referring to established theoretical models (Schein, Hofstede, Cameron & Quinn) and the cultural specificity of the university environment; outlining the model in which these values influence the quality of education, organizational efficiency, and the academic experience of students and teachers; measuring the degree of acceptance and manifestation of four fundamental values (university mission, interpersonal collaboration, innovation, and organizational climate) by applying a questionnaire to 35 university teaching staff; reflecting on strategic directions for institutional development based on the consolidation of the identified fundamental values. Previous studies present the opinions of authors renowned for their representative works: Schein (1985) showed that common values, norms, and assumptions constitute the core of organizational culture; Hofstede (2011) and Hofstede Insights developed the Multi-Focus model, which allows for the investigation of cultural dimensions at the institutional level; Cameron and Quinn (2011) proposed the Competing Values Framework for diagnosing cultural typologies. In the academic context, the works reflected in Manning, 2000; Kuh & Whitt, 1988; Warter, 2019 emphasize that universities, as complex organizations, define their culture through mission, traditions, disciplinary subcultures, and socialization processes. The approach to the fundamental values of organizational culture in higher education is based on a theoretical and applied analysis of organizational culture values, which includes the interpretation of cultural levels (artifacts, stated values, basic assumptions) and organizational functions (internal integration and external coordination – Furnham & Gunter, 1993). At the same time, the influence of knowledge management (Mudor, 2014) and organizational communication (Bess & Dee, 2008; Taguiam, 2025) on institutional efficiency is examined. From an applied perspective, the questionnaire results show that interpersonal relationships and collaboration obtained an average score (M = 3.3), which indicates the existence of potential for improving the climate of communication and interdepartmental cooperation. The results highlight differences in intensity between the fundamental values analyzed. Innovation, adaptability, and change management (M = 2.9, medium level) are partially manifested, which shows that although the university values innovation, its concrete application remains fragmented. In contrast, the organizational climate and social engagement (M = 3.6, high level) outline a positive perception of the academic environment, characterized by mutual support and participation, even if satisfaction sometimes remains fluctuating. These results confirm the hypothesis that fundamental values are not evenly distributed and that some dimensions need to be strengthened through institutional strategies. The value of the research lies in providing an integrated perspective on organizational culture in higher education by correlating international theories with the realities of the academic environment. The study adds value by identifying gaps in the literature and highlighting the role of fundamental values in creating an organizational climate conducive to academic development and institutional efficiency. The fact that the mission and organizational climate are perceived at a high level, while collaboration and innovation are at medium levels, provides a balanced picture of strengths and vulnerabilities that can guide managerial and academic interventions.